Simulation of thalamic prosthetic vision: reading accuracy, speed, and acuity in sighted humans - Vurro, Milena; Crowell, Anne Marie; Pezaris, John S. (Frontiers in Human Neuroscience, 2014)
The psychophysics of reading with artificial sight has received increasing attention as visual prostheses are becoming a real possibility to restore useful function to the blind through the coarse, pseudo-pixelized vision they generate. Studies to date have focused on simulating retinal prostheses; here we extend that work to report on thalamic designs. This study examined the reading performance of normally sighted human subjects using a simulation of three thalamic visual prostheses that varied in phosphene count, to help understand the level of functional ability afforded by thalamic designs in a task of daily living. Reading accuracy, reading speed, and reading acuity of 20 subjects were measured as a function of letter size, using a task based on the MNREAD chart. Results showed that fluid reading was available with appropriate combinations of letter size and phosphene count, and performance degraded smoothly as font size was decreased, with an approximate doubling of phosphene count resulting in an increase of 0.2 logMAR in acuity. Results here were consistent with previous results from our laboratory. Results were also consistent with those from the literature, despite using naive subjects who were not trained on the simulator, in contrast to other reports.